Optimisation of microfabricated devices for neural circuit modelling - Sophie Oakley (2022)
The incidence of neurodegenerative diseases such as Parkinson’s and Alzheimer’s disease is on the rise in line with the increase in ageing populations. More effective, curative treatments are required to stem the socio-economic burden of these diseases, but more accurate and complex models are required to develop these. The current gold standard model of such diseases is the primary rodent model. These models are simplified and do not accurately recapitulate the human brain in health or disease, leading to late-stage clinical trial failure. To evolve these platforms and facilitate development, we must transition into more accurate human neuronal models. This thesis presents the development and optimisation of a humanised microfluidic in vitro neuronal model using simple 2-port compartmentalised microfabricated devices to culture SH-SY5Y neurons.The differentiation protocol of SH-SY5Y neurons was optimised to promote long, unbranched, functional neurons suitable for crossing patterned microchannels for circuit unidirectionality. Functionality of these optimised neurons was assessed using both calcium imaging and a multi-electrode array (MEA) to characterise both spiking and bursting activity. SH-SY5Y neurons were then introduced into PDMS devices and successfully differentiated and spontaneous electrophysiological activity recorded over several weeks. This thesis provides a novel perspective on SH-SY5Y differentiation for use in neuronal circuit modelling and long-term studies previously unexplored in the literature. Further development of this model, connecting two isolated populations of neurons and the application of the designs considered in this thesis would make a strong candidate for an accessible and adaptable neuronal circuit model of neural health and disease.